HUBUNGAN ARCUS PEDIS DENGAN KESEIMBANGAN STATIS PADA ANAK USIA 9-12 TAHUN DI SDN GONILAN 02 - Risa Fitri Kurniati; Adnan Faris Naufal (Bajang Institute, 2024)
Background: the ability of children to be able to perform physical activities in a coordinated manner is needed to support and support physical activities so as to improve their achievements. Therefore, in childhood, physical development must always be paid attention to, especially in the development of the arcus pedis, because in childhood if the arcus pedis of children who do not grow normally will be able to cause several disorders, one of which disorders that can occur is balance disorders, while balance is a very vital body function for humans as well as the five senses. Objective: The purpose of this study was to determine whether there is a relationship between arcus pedis and static balance in children aged 9-12 years at Gonilan 02 Elementary School. Method: this study used a cross sectional study design method, the sample size was 84 children with purposive sampling technique and random samples (randbetween), using the Kolmogorov-smirnov normality test and the spearment rho test. Results: esults: from the results of the study from the Spearmen's rho test of the arcus pedis with static balance, a significant value of p = 0.017> 0.05 was obtained so that it could be concluded that there was a relationship between the arcus pedis and static balance for a value of r = 0.260 which means that the level of relationship is weak and the data is positive, where the arcus pedis has increased, the static balance has increased. Conclusion: Based on the results of the research that has been done, it shows that there is a relationship between arcus pedis and static balance in children aged 9-12 years at Gonilan 02 Elementary School.